2018
DOI: 10.1186/s12933-018-0775-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of dapagliflozin on left ventricular diastolic function of patients with type 2 diabetic mellitus with chronic heart failure

Abstract: BackgroundThe objective of this study was to investigate the impact of sodium glucose cotransporter type 2 (SGLT2) inhibitors on left ventricular (LV) diastolic function of type 2 diabetes mellitus (T2DM) patients with heart failure (HF).MethodsThis trial was a prospective multicenter study of 58 T2DM patients with stable HF at five institutions in Japan. Patients who had been taking at least one antidiabetic drugs other than SGLT2 inhibitors started the administration of 5 mg/day of dapagliflozin. The physica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
139
2
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(157 citation statements)
references
References 32 publications
13
139
2
3
Order By: Relevance
“…A recent report showed that patients with E/e ′ of diabetes and HF were improved by SGLT2 inhibitor. However, the mechanism is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report showed that patients with E/e ′ of diabetes and HF were improved by SGLT2 inhibitor. However, the mechanism is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with T2DM who had or were at risk for atherosclerotic cardiovascular disease, treatment with dapagliflozin robustly resulted in a lower rate of cardiovascular death or HHF [125,126], and subgroup analysis showed that dapagliflozin reduced HHF in patients with and without HFrEF [127]. Another prospective multicentre trial showed the beneficial effect of dapagliflozin on LV diastolic functional parameters for T2DM patients with HF [128]. CREDENCE and CANVAS supported that canagliflozin significantly reduced major cardiovascular events in patients with T2DM and cardiovascular disease [129][130][131].…”
Section: Sodium-glucose Cotransporter-2 Inhibitors (Sglt-2is)mentioning
confidence: 99%
“…VNS NECTAR-HF [92,93], ANTHEM-HF [94,95] Comorbidities T2DM SGLT-2i: Empagliflozin EMPA-REG OUTCOME [112,114,122], EMPRISE [124]; Dapagliflozin: DECLARE-TIMI 58 [117,[125][126][127], Soga et al [128]; DAPA-HF [118,119]; Canagliflozin: CANVAS [120,131,132], CREDENCE [129,130]. GLP-1: Liraglutide: LEADER [141], LIVE [142], and FIGHT [143]; Semaglutide: SUSTAIN-6 [144] DPP4i: Sitagliptin: TECOS [146,147]; Saxagliptin: SAVOR-TIMI 53 [148]; Vildagliptin: VIVIDD [149]; Linagliptin: CARMELINA [150];…”
Section: Treatments Key Trialsmentioning
confidence: 99%
“…14 In clinical trials, the use of SGLT2 inhibitors has been shown to reduce the quantity of epicardial adipose tissue (independently of effect on body weight), [35][36][37] and these drugs ameliorate the inflammation of adipose tissue surrounding the heart and great vessels 38,39 and the associated abnormalities of cardiac filling and aortic distensibility in both experimental and clinical HFpEF. 18,[40][41][42] Furthermore, SGLT2 inhibitors act to inhibit sodium reabsorption in the proximal renal tubules, in which the majority of renal sodium retention occurs [43][44][45] ; this action explains the marked reduction in plasma and/or interstitial volume and haemoconcentration seen in randomized controlled trials in type 2 diabetes. 25,46 Moreover, SGLT2 inhibitors can attenuate renal inflammation and fibrosis.…”
Section: Sample Size Calculations and Study Conductmentioning
confidence: 99%